Effects of Sacubitril-Valsartan in Heart Failure With Preserved Ejection Fraction in Patients Undergoing Peritoneal Dialysis - Fu, Sha; Xu, Zhenjian; Lin, Baojuan; Chen, Junzhe; Huang, Qiuyan; Xu, Yanchun; Xu, Anping; Chen, Yangxin; Tang, Ying (Frontiers in Medicine, 2021)
Aims: The effect of the angiotensin receptor–neprilysin inhibitor (ARNI) sacubitril-valsartan in patients with heart failure with preserved ejection fraction (HFpEF) remains unclear, and data on ARNI treatment in peritoneal dialysis (PD) patients are lacking. The present study was designed to assess the efficacy and safety of sacubitril-valsartan in patients with HFpEF undergoing peritoneal dialysis. Methods and Results: End-stage kidney disease (ESKD) patients undergoing PD for 3 months with New York Heart Association (NYHA) class II–IV heart failure, ejection fraction of 50% or higher, and elevated levels of N-terminal pro–B-type natriuretic peptide (NT-proBNP) were assigned to receive sacubitril-valsartan. Patients were followed up regularly after medication treatment. The alterations in clinical and biochemical parameters before and after taking sacubitril-valsartan (generally 50–100 mg b.i.d) were investigated, and safety was also assessed. Twenty-one patients were recruited in this study. Compared with baseline levels, NT-proBNP levels [9769.0 (3093.5–21941.0) vs. 3034.0 (1493.2–6503.0), P = 0.002], and heart rate [80.0 (74.5–90.5) vs. 75.0 (70.3–87.0), P = 0.031] were markedly decreased after treatment with sacubitril-valsartan. Signs and symptoms of heart failure (21/21 vs. 15/21, P = 0.021) were obviously alleviated, NYHA classification and E/e' ratio showed a notable trend of improvement after 3–12 months of follow-up. None of the patients showed adverse drug reactions. Conclusions: The present data suggested that sacubitril-valsartan treatment in patients with HFpEF undergoing PD was effective and safe.